Poloxamer 188 (P188) as a Membrane Resealing Reagent in Biomedical Applications - Moloughney, Joseph G. (2012)
Maintenance of the integrity of the plasma membrane is essential for maintenance of cellular function and prevention of cell death. Since the plasma membrane is frequently exposed to a variety of mechanical and chemical insults the cell has evolved active processes to defend against these injuries by resealing disruptions in the plasma membrane. Cell membrane repair is a conserved process observed in nearly every cell type where intracellular vesicles are recruited to sites of membrane disruption where they can fuse with themselves or the plasma membrane to create a repair patch. When disruptions are extensive or there is an underlying pathology that reduces the membrane repair capacity of a cell this defense mechanism may prove insufficient and the cell could die due to breakdown of the plasma membrane. Extensive loss of cells can compromise the integrity and function of tissues and leading to disease. Thus, methods to increase membrane resealing capacity could have broad utility in a number of disease states. Efforts to find reagents that can modulate plasma membrane reseal found that specific tri-block copolymers, such as poloxamer 188 (P188, or Pluronic F68), can increase the structural stability and resealing of the plasma membrane. Here we review several current patents and patent applications that present inventions making use of P188 and other copolymers to treat specific disease states such as muscular dystrophy, heart failure, neurodegenerative disorders and electrical injuries, or to facilitate biomedical applications such as transplantation. There appears to be promise for the application of poloxamers in the treatment of various diseases, however there are potential concerns with toxicity with long term application and bioavailability in some cases.